International external validation of a stratification tool to identify branch‐duct intraductal papillary mucinous neoplasms at lowest risk of progression. Issue 2 (24th February 2022) - Overbeek, Kasper A.; van Leeuwen, Nikki; Tacelli, Matteo; Anwar, Muhammad S.; Yousaf, Muhammad N.; Chhoda, Ankit; Arcidiacono, Paolo Giorgio; Gonda, Tamas A.; Wallace, Michael B.; Capurso, Gabriele; Farrell, James J.; Cahen, Djuna L.; et al.
Abstract: Background: Identifying branch‐duct intraductal papillary mucinous neoplasms (BD‐IPMNs) at lowest risk of progression may allow for a reduced intensity of surveillance. Objective: We aimed to externally validate the previously developed Dutch‐American Risk stratification Tool (DART‐1; https://rtools.mayo.edu/DART/ ), which identifies cysts at low risk of developing worrisome features (WFs) or high‐risk stigmata (HRS). Methods: Three prospective cohorts of individuals under surveillance for BD‐IPMNs were combined, independent from the original development cohort. We assessed the performance (discrimination and calibration) of DART‐1, a multivariable Cox‐proportional logistic regression model with five predictors for the development of WFs or HRS. Results: Of 832 individuals (mean age 77 years, SD 11.5) under surveillance for a median of 40 months (IQR 44), 163 (20%) developed WFs or HRS. DART‐1's discriminative ability (C‐statistic 0.68) was similar to that in the development cohort (0.64–0.72) and showed moderate calibration. DART‐1 adequately estimated the risk for patients in the middle risk quintile, and slightly underestimated it in the lowest quintiles. Their range of predicted versus observed 3‐year risk was 0%–0% versus 0%–3.7% for Q1; 0.3%–0.4% versus 3%–11% for Q2; and 2.6%–3% versus 2.4%–9.8% for Q3. The development of WFs or HRS was associated with pancreatic cancer ( p  < 0.001). Vice versa, in absence of WFs or HRS, the risk of malignancy was low (0.3%). Conclusions: The performance of DART‐1 to predict the development of WFs or HRS in BD‐IPMN was validated in an external international cohort, with a discriminative ability equal as in the development cohort. Risk estimations were most accurate for patients with BD‐IPMNs in the middle risk quintile and slightly underestimated in the lowest quintiles.